The effects of age and cohort on household saving - Petri Mäki-Fränti (Bank of Finland, 2022)
According to the standard life cycle model, household saving rate should peak at the best working age and turn then to decline so that households dissolve their savings after retirement. This study examines, how age and birth cohort affect the saving behavior of the Finnish households. A synthetic panel data is used to estimate an empirical age-cohort-period model of income, consumption and saving rate of the households. The results suggest that the Fnnish households continue saving even in the old age and younger cohohorts tend to save more than the older ones. Thus, a projected aggregate saving rate of the Finnish economy will slightly increase during the next two decades.
urn:nbn:fi:bof-202208301349
Keywords: E21; J11; 330; population aging; household saving; age-cohor-period models; synthetic cohort